Are Extremely Low Gestational Age Newborns Born to Obese Women at Increased Risk of Cerebral Palsy at 2 Years?. (March 2018) - van der Burg, Jelske W.; O'Shea, T. Michael; Kuban, Karl; Allred, Elizabeth N.; Paneth, Nigel; Dammann, Olaf; Leviton, Alan
The authors hypothesized that the risk of cerebral palsy at 2 years in children born extremely preterm to overweight and obese women is increased relative to the risk among children born to neither overweight nor obese women. In a multicenter prospective cohort study, the authors created multinomial logistic regression models of the risk of diparetic, quadriparetic, and hemiparetic cerebral palsy that included the prepregnancy body mass index of mothers of 1014 children born extremely preterm, cerebral palsy diagnoses of children at 2 years, as well as information about potential confounders. Overweight and obese women were not at increased risk of giving birth to a child who had cerebral palsy. The risk ratios associated with overweight varied between 1.1 for quadriparesis (95% CI = 0.5, 2.1) to 2.0 for hemiparesis (95% CI = 0.4, 9.8). The risk ratios associated with obesity varied between 0.7 for diparesis (95% CI = 0.2, 2.5) to 2.5 for hemiparesis (95% CI = 0.4, 13).